Substitusi Jagung dengan Campuran Tepung Gaplek-Dedak Halus dan Methionin dalam Ransum Ayam Broiler - I.K. Amrullah; A.D. Hasjmy; B. Rahmaniyah; A.U. Faridlah; R. Mutia (Buletin Ilmu Makanan Ternak, 1990)
Some of feed factories in Indonesia produce their uncompleted ration, called concentrates, that should be mixed with some corn and rice bran to make a complete ration. A combination of 60% of corn and 40% of the concentrate in starter diet and of 60% corn, 10% of rice bran and 30% of the concentrate in finisher diet were recomended.An experiment had been conducted to study the possibility of cassava meal (peeled or unpleeled) and rice bran mixed and also with or without methionine supplementation to substitute corn in broiler diet. A combination of one third of cassava meal and two third of rice bran had similar nitrogen content with 60% of corn. One hundred day old chicks (D.O.C.) strain Arbor Acres-CP 707 divided into 20 groups. Five treatments : Ro (recomended feedmill ration), R1 (using peeled cassava meal and rice bran mixed), R2 (using unpleeled cassava meal and rice bran mixed), R1+M (R1+0.2% methionine), R2+M(R2+0.2% methionine) were used.The experiment indicated that R1 gave the best result in body weight gain and feed consumption expect for feed conversion. In the study the methionine supplementation did not improve performances. The income over feed and chick cost (IOFC) of the broiler ration contained unpeeled cassava meal and rice brand mixed was higher than that control (R0). This result is economically important for broiler farmers.